Chromosome banding studies in wheat (Triticum aestivum L. em. Thell.) - Van Niekerk, H. A.(Hugo Amos) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. Agric.) -- University of Stellenbosch, 1988.